Modelling of paste boriding process. (August 2015) - Kouba, R.; Keddam, M.; Kulka, M.
Abstract : In this work, a new model was suggested to simulate the paste boriding process. This model was based on the numerical solving of the diffusion equations in both boride layer and substrate by taking into account the displacement of (Fe2 B/substrate) interface. This diffusion problem with moving boundary was solved via a front tracking method. The numerical resolution was achieved by the finite difference method using an implicit scheme. The suggested model was able to predict the boride layer growth kinetics and the boron concentration profiles. The present model was validated by comparing the simulation results with the experimental data available in the literature. The obtained results were also compared to the models previously reported.